GRAMMATICAL EXPRESSION OF SYNONYMS IN TURKISH LANGUAGE IN “MUHAKAMAT UL-LUGATAYIN” BY ALISHER NAVAI - Safarova Dildora Baxtiyor qizi (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
In the article, Alisher Navoi's work "Muhokamat ul-lughatayin" discusses the grammatical nature of synonyms in the Turkish language, the importance of meaning in poetry. The poet's ability to create a poetic image through these words is analyzed.